Development of financial systems in 1995-2014 – a factor analysis - Iwanicz-Drozdowska, Małgorzata; Smaga, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the research was to analyse financial system development patterns for both 19 post-communist European economies and 21 non-post-communist (advanced) countries over the 1995-2014 period. The use of a factor analysis allowed for identifying two unobservable factors which account for most of the variance of the 9 observed variables characteristic of the economic and financial development, the banking sector’s standing and the structure of the financial sector. Identified factors represent the financial system development and growth of the banking sector, but their roles differ among the analysed groups of countries. The banking sector is a significant driving force of development in both cases. Yet, in advanced economies, a certain role is also played by the stock market, which is not the case for post-communist countries. The results show that there is higher homogeneity in the financial system development patterns in post-communist countries, while the roles of both factors are more heterogeneous among advanced economies. Lastly, the results provide evidence that the global financial crisis did not cause a permanent structural change in these two processes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 47-60
Keywords: post-communist countries; financial system; factor analysis; kraje postkomunistyczne; system finansowy; analiza czynnikowa